Ferrous versus Ferric Oral Iron Formulations for the Treatment of Iron Deficiency: A Clinical Overview - Palacios Santiago (The Scientific World Journal)
Iron deficiency anaemia represents a major public health problem, particularly in infants, young children, pregnant women, and females with heavy menses. Oral iron supplementation is a cheap, safe, and effective means of increasing haemoglobin levels and restoring iron stores to prevent and correct iron deficiency. Many preparations are available, varying widely in dosage, formulation (quick or prolonged release), and chemical state (ferrous or ferric form). The debate over the advantages of ferrous versus ferric formulations is ongoing. In this literature review, the tolerability and efficacy of ferrous versus ferric iron formulations are evaluated. We focused on studies comparing ferrous sulphate preparations with ferric iron polymaltose complex preparations, the two predominant forms of iron used. Current data show that slow-release ferrous sulphate preparations remain the established and standard treatment of iron deficiency, irrespective of the indication, given their good bioavailability, efficacy, and acceptable tolerability demonstrated in several large clinical studies.